Improvement of the Mechanical Properties of Concrete for Paving by Adding Interlocking Steel Fibers - Lisbeth Rodríguez Santa Cruz; Pedro Ramón Patazca Rojas (International Journal of Sustainable Construction Engineering and Technology, 2024)
This article describes the work carried out to investigate the behavior of concrete by adding interlocking steel fibers in different proportions (0%, 1%, 1.5%, 2% and 2.5%) for rigid pavements, said addition was made in percentage as an addition to the concrete. With an f'c of 280 kg/cm2 for the standard concrete, the tests were carried out to determine its resistance to compression in 28 days, resistance to flexion in 28 days, and resistance to diametral traction in 28 days. It was obtained as results that the optimal percentage for the compression resistance test was 1%, reaching a resistance of 350 kg/cm2 at 28 days, for the flexion test the optimal percentage was 2.5%, the best The value obtained in the tensile test was the addition of 2.5% and finally in the ASTM C944 test it was obtained as a result that the percentage of 2.5% is the best of all where the wear is minimal by 0.010%. The rigid concrete used for concrete paving has a potential use in the construction of road infrastructures and applying the addition of interlocking steel fibers only improves some characteristics of the concrete, such as flexion and traction.